How Student Affairs Education Limits Spiritual, Religious, and Secular Identity Exploration: A Qualitative Study of Graduate Students' Educational Experiences. Issue 4 (1st November 2020) - Burchett, Matthew; Glanzer, Perry
Abstract: Little scholarship explores the attention to religious, spiritual, and secular identity in the graduate preparation of student affairs professionals. To address this gap, we undertook a phenomenological examination of the experiences of second-year graduate students in four elite master of education programs with respect to these identities. We found that both secularists and devout religious believers experienced a marginalization that chilled discussions about these identities and their willingness to share their own identities. Their view that other students and professors did not perceive spiritual, secular, or religious identity development as important amplified their fear and sense of marginalization.